Bitter Taste Receptor Antagonists Inhibit the Bitter taste of Canola Meal Extract in Chickens - Kawabata, Fuminori (J Poult Sci, 2020)
Canola meal (CM) is a commonly used feedstuff; however, it is known to be bitter, and chickens have a low preference for it. The purpose of this study was to seek clarity regarding the taste quality of CM and find methods to increase the preference for CM by chickens. We examined whether CM activates the bitter taste receptors in chickens, whether chickens show aversive responses to CM, and whether an antagonist for bitter taste receptors inhibits the bitterness of CM. Using the Ca(2+) imaging technique, we showed that CM contains bitter compounds, which activate the bitter taste receptors in chickens. Further, we showed that 6-methoxyflavanone (6-meth), an antagonist for the bitter taste receptors in chickens, inhibits the activation of these receptors by CM extract. Although chickens showed a low preference for the solution of the CM extract, their preference was improved by adding 6-meth in behavioral tests. These results suggest that the preference for CM could be improved by inhibiting the bitter taste receptors in chickens.